2021
DOI: 10.3390/antibiotics10101177
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Revision Risk Analysis after Single- vs. Two-Stage Revision Total Knee Arthroplasty in Periprosthetic Joint Infection: A Retrospective Tertiary Center Analysis

Abstract: Periprosthetic joint infection (PJI) remains one of the most common causes of revision knee arthroplasty. Controversy continues to surround the proper operative technique of PJI in knee arthroplasty with single- or two-stage replacement. Significant variations are seen in the eradication rates of PJI and in implant survival rates. This detailed retrospective analysis of a single tertiary center is intended to provide further data and insight comparing single- and two-stage revision surgery. A retrospective ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…After excluding duplicates, 343 studies were included, and after evaluation of the title and abstract, 21 studies were analyzed. After assessing the eligibility of the full-text articles according to the inclusion and exclusion criteria and screening the bibliography of each article to find additional relevant publications, 18 clinical studies were selected and included in this systematic review [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. The PRISMA flowchart with the research strategy is shown in Fig.…”
Section: Search Strategy and Study Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…After excluding duplicates, 343 studies were included, and after evaluation of the title and abstract, 21 studies were analyzed. After assessing the eligibility of the full-text articles according to the inclusion and exclusion criteria and screening the bibliography of each article to find additional relevant publications, 18 clinical studies were selected and included in this systematic review [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. The PRISMA flowchart with the research strategy is shown in Fig.…”
Section: Search Strategy and Study Screeningmentioning
confidence: 99%
“…Eighteen clinical studies [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] were included in the final analysis (Fig. 1) [17].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Although two-stage revision concepts ensure satisfactory long-term results [ 21 , 22 , 23 ], one-stage revision approaches are of particular interest [ 24 , 25 ] due to reduced functional impairment and mortality [ 23 , 26 ]. Overall, treatment failure for re-infection rates following arthroplasty exchange ranges between 10% and 25% [ 27 , 28 , 29 ]. For years, most authors attributed the sufficient treatment of PJI solely to multiple-stage revision approaches [ 18 , 19 , 27 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, treatment failure for re-infection rates following arthroplasty exchange ranges between 10% and 25% [ 27 , 28 , 29 ]. For years, most authors attributed the sufficient treatment of PJI solely to multiple-stage revision approaches [ 18 , 19 , 27 , 30 ]. However, recent data prove satisfactory treatment results following single-stage revision surgery as long as patients are adequately selected for eligibility [ 28 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tuecking et al performed a detailed revision risk analysis after single- vs. two-stage revision surgery in the management of knee PJIs [ 7 ]. No significant difference was found between both groups in overall and implant survival with respect to reinfection.…”
mentioning
confidence: 99%